Defending the environment: civil society participation in resolving investment-related environmental claims - Lin, Wei-Chung (2016)
Today it is widely recognised that international investment activities can bring significant economic benefits for host countries. To promote a favourable investment climate, international organisations were set up to facilitate the settlement of foreign investment disputes, or to provide financial insurance for investors against non-commercial risks. Moreover, international financial institutions offer finance for governments or private enterprises to implement investment projects. States have also concluded international investment agreements to provide guarantees on the treatment and protection of foreign investors. Meanwhile, however, these investment activities can also create environmental problems for host countries and lead to human suffering.